Reserving a Seat at the Table: Examining the Impact of the Women’s Reservation Act - Dakwar, Jowaher George (Journal of Social Science and Humanities, 2025)
The need of empowerment for women in politics is unquestionable, as it is essential for achieving true gender equally and creating inclusive societies. Women make up roughly half of the population, and their perspectives and experiences must be represented in decision - making processes. Empowering women in politics not only upholds democratic principles but also lead to more balanced and comprehensive policies. As rightly said by Naila Kabeer “If women’s productive activities were better understood, policy could be designed to support rather than invisibles their contributions” (LSE Research 2016) When women have equal opportunities to participate in politics, it fosters diverse leadership, challenges gender stereotypes and addresses issues like gender based violence and discrimination effectively. By promoting women’s political empowerment, we take a significant step towards building fairer and more just societies where everyone’s voices are heard and valued. The condition of women in society has evolved significantly over last two decades with noticeable progress in many areas but persistent challenges in others. In various fields like education, workforce participation, political representation, legal reforms, technology and communication, reproductive rights, economic empowerment significant development and improvement has been seen. But women as a community still seems lacking somewhere a lot. This paper will try to find out that why reservation is needed for women in policy making decisions and what will be the impact of Reservation Bill on the women and what other people think about this bill. For this purpose 150 respondents from college were taken randomly to find out how this bill proves to break a glass ceiling (overcoming the barriers set to prevent access to advancement.) for the betterment of women in policy making issues.